Autopsy findings in an atypical case of occult massive fatal pulmonary embolism in a backdrop of hyperhomocysteinemia - Pratibha Misra; Arijit Kumar Ghosh; Aneeta Jassar (Wolters Kluwer Medknow Publications, 2018)
A 43-year-old apparently healthy male presented with fever and presyncope. He was suspected to have massive pulmonary thromboembolism based on the clinico-biochemical profile. Despite aggressive thrombolytic therapy, he succumbed to his illness within 12 h of admission. Postmortem examination showed massive pulmonary thromboembolism and hyperhomocysteinemia with low high-density lipoproteins (HDL) cholesterol with antemortem blood sample. Herein, we report autopsy findings in a rare case of a young male with occult massive pulmonary thromboembolism without deep vein thrombosis, who had an atypical clinical presentation and was found to have underlying hyperhomocysteinemia and decreased HDLc. An acute, massive PE can present a diagnostic challenge due to the rate and severity of decompensation seen in afflicted patients. A high index of suspicion is required for early detection of pulmonary embolism in a young patient with atypical presentation and without obvious risk factors.